Comparison of the accuracy of patients' recall of the content of telephone and face-to-face consultations: an exploratory study. Issue 1028 (3rd March 2011) - McKinstry, Brian; Watson, Philip; Elton, Robert A; Pinnock, Hilary; Kidd, Gillian; Meyer, Barbara; Logie, Robert; Sheikh, Aziz
Abstract : Background: To comply with an action plan patients need to recall information accurately. Little is known about how well patients recall consultations, particularly telephone consultations increasingly used to triage acute problems. Purpose of study: This was an exploratory study to measure how accurately patients recall the content of face-to-face and telephone consultations and what factors may be associated with accurate recall. Study design: In Scotland in 2008, the advice (diagnoses; management plan(s); and safety-netting arrangements) given in audio recorded face-to-face and telephone consultations was compared with the advice recalled by patients at interview approximately 13 days later. Patients also performed a memory test. Interactions were sought between accurate recall, consultation type, and factors postulated to influence recall. Results: Ten general practitioners (GPs) and 175 patients participated; 144 (82%) patients were interviewed. Patients recalled most important components of telephone and face-to-face consultations equally accurately or with only minor errors. Overall, patients presenting multiple problems (p<0.001), with brain injury (p<0.01) or low memory score (p<0.01) had reduced recall. GPs rarely used strategies to improve recall; however, these were not associated with improved recall. Conclusions: Contrary to previous hospital based research, patients tended to remember important components of both face-to-face and telephone consultations—perhaps reflecting the familiar, less anxiety provoking environment of primary care. The unsuccessful use of strategies to improve recall may reflect selective use in cognitively impaired patients. Clinicians should compensate for situations where recall is poorer such as patients presenting multiple problems or with brain injury. Patients might be advised to restrict the number of problems they present in any one consultation.